DASAR PENGURUSAN KOLEKSI SARAWAKIANA DI PUSTAKA NEGERI SARAWAK : Sarawakiana Collection Management Policy In Sarawak State Library - Athirah Shahira'a, Abdullah; Rahah, Hasan; Shaik Azahar, Shaik Hussain (UNISZA, 2021)
The purpose of this study is to determine which policies are in place in the Sarawak State Library for the management of the Sarawakiana collection. Every collection at a large or small institution contains significant value in terms of history, heritage, treasures, aesthetics, and other factors. In the management of a collection, policy is very important. Most of organisation’s management is done in accordance with the plan or plans that have been made to meet in the collection's maintenance. The researcher employed qualitative approaches such as interviews and documentation.